Does Urbanization promote Development ? - Jayadevan, C. M. (Archives of Business Research, 2020)
Urbanization can influence the economic growth and development. Urbanization experienced in the last three decades really promoted economic growth and development. Using a sample of 107 countries over the period 1991-2018, this study verifies and finds the support for the hypothesis that urbanization promotes development with the help of structural equation modeling.